Non-Accidental burn injuries in adults admitted at mankweng burns unit - Mzezewa, Salathiel Zhou; makhuvha, livhuwani (Jour Med Resh and Health Sci, 2020)
Abstract Introduction Burns are a serious public health problem responsible for mortality and morbidity such as infection, contractures, and psycho-social disability. Aims and Objectives To obtain information on non-accidental burn injuries admitted to our burns unit. To record the outcome. Methods All patients with a history of non-accidental burn injuries from January 2019 to August 2020 were prospectively included in this study. A data collection tool was created which consisted of data on age, gender, causative agents of burns, mechanism/circumstances that led to injury, total body surface area (TBSA) involved, and the patient’s outcome. Results We admitted 38 patients. 22 males and 16 females. The mechanisms were intimate partner related violence 21, religious and traditional beliefs 5, self-inflicted 3, mob assault 1, robbery 2, alcohol-related conflicts 3, unclear mechanisms 3. The causative agents were scald 20, open flame 15 and chemical burns 3. The median age was 35,63(19-64) years. The median total body surface area was 24,4 (3-80) %. Mortality was 11(29%). Conclusion Burn injuries as a result of intimate partner-related violence were the leading reason for admission at 55,26%. Mortality was highest among those admitted following religious and traditional beliefs burns. The mortality was 29%.